Hydrogen bonding to carbonyl oxygen of nitrogen-pyramidalized amide – detection of pyramidalization direction preference by vibrational circular dichroism spectroscopy. Issue 21 (18th February 2016) - Wang, Siyuan; Taniguchi, Tohru; Monde, Kenji; Kawahata, Masatoshi; Yamaguchi, Kentaro; Otani, Yuko; Ohwada, Tomohiko
Abstract : Hydrogen-bonding to carbonyl of nitrogen-pyramidalized bicyclic β-proline amides can switch the preferred nitrogen-pyramidalization direction, as detected by VCD spectroscopy. Abstract : Nitrogen-pyramidalization of amide increases electron density on nitrogen and decreases that on carbonyl oxygen. We identified hydrogen-bonding to carbonyl of nitrogen-pyramidalized bicyclic β-proline derivatives by crystallography, and by NMR and vibrational circular dichroism (VCD) spectroscopy in solution. Such hydrogen-bonding can switch the preferred nitrogen-pyramidalization direction, as detected by VCD spectroscopy.